A influência das plantas de cobertura e da escarificação mecânica nos atributos físicos do solo - Nunes, Paulo Rogério Amaral (2025)
Soil compaction in no-till farming occurs mainly due to the pressure of agricultural machinery traffic, which is heavier and has a greater number of operations per crop that causes damages its physical characteristics. The aim of this work was to explore alternatives to improve the physical quality of agricultural soil using cover crops with or without the application of mechanical scarification in different production environments that present different production potential especially in soybean crops. The experiment was made in 2020 at Polytechnic College of UFSM. The soil in the experimental area was classified as Red Argisol with an average of 21.5% clay in the 0 to 20 cm layer. The experimental design was a split-block design with three repetitions. The treatments, which consisted of a mix (polyculture) of cover crops, were evaluated in the main plot T1 - RX 210® Black oats (Avena strigosa), white oats (Avena sativa), rye (Secale cereale), fodder radish (Raphanus sativus L.), and “Japanese Minowase” fodder radish (Brassica napus L.) at a density of 50 kg ha-1. T2 - RX 610®: Black oats, vetch, hairy vetch, and “Japanese Minowase” fodder radish at a rate of 45 kg ha-1. T3 - Rye BRS Serrano. T4 - Fallow: A control plot consisting of spontaneous species.The soil was scarified before the polyculture was sown. The evaluations of soil physical quality included: stability of soil aggregates, soil density and porosity, hydraulic conductivity, and water infiltration into the soil. It was observed that the effect of scarification on improving soil physical quality did not persist until the time of the physical evaluation, which was 06 months after the operation. Overall, the soil showed critical values of macroporosity, equal to or less than 10%, especially at a depth of 10-20 cm, due to the history of conventional cultivation adopted in the area before the implementation of the no-till system. Water infiltration in both cumulative and constant rates was relatively low regardless of the type of treatment. It is likely that the high infestation of volunteer fodder radish in the fallow control treatment contributed to the lack of distinction compared to the cover crop polycultures.